2017
DOI: 10.1007/s10532-017-9793-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and kinetics of ANAMMOX granular sludge with pH shock in a sequencing batch reactor

Abstract: As an efficient and cost-effective nitrogen removal process, anaerobic ammonium oxidation (ANAMMOX) could be well operated at suitable pH condition. However, pH shock occurred in different kinds of wastewater and affected ANANNOX process greatly. The present research aimed at studying the performance and kinetics of ANAMMOX granular sludge with pH shock. When influent pH was below 7.5, effluent NH -N deviated from theoretical value. Longer recovery time from pH 9.0 than from pH 6.0 indicated that alkaline surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 47 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…The high value of R 2 (0.9635, 0.9857, 0.9815) from the three models dictated a good linear relationship between the experimental data and the predicted value. The t‐value (0.06, 2.54E‐06, 2.56E‐05) were much lower than the value of t crit (0.703) indicating that the models were unbiased . These findings demonstrated that all three models could be suitably applied for determining the TNRE with the addition of mannitol in a SAD process.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The high value of R 2 (0.9635, 0.9857, 0.9815) from the three models dictated a good linear relationship between the experimental data and the predicted value. The t‐value (0.06, 2.54E‐06, 2.56E‐05) were much lower than the value of t crit (0.703) indicating that the models were unbiased . These findings demonstrated that all three models could be suitably applied for determining the TNRE with the addition of mannitol in a SAD process.…”
Section: Resultsmentioning
confidence: 87%
“…The t-value (0.06, 2.54E-06, 2.56E-05) were much lower than the value of t crit (0.703) indicating that the models were unbiased. [43][44][45] These findings demonstrated that all three models could be suitably applied for determining the TNRE with the addition of mannitol in a SAD process. The kinetic analysis for high mannitol inhibition recovery period is shown in Figs S4 and S2.…”
Section: Kinetic Analysismentioning
confidence: 75%
“…Thus, the CANON process was severely inhibited by the alkaline shock. As Li et al [ 11 ] reported, the effect of an alkaline pH (9.0) shock on the performance of anammox granular sludge was much more severe than that of an acidic pH (6.5) shock, and the alkaline condition disintegrated anammox granules. Based on the impact of influent pH of 4 and 10 for 12 h, Yu and Jin [ 35 ] also found a loss of anammox performance only in alkaline condition.…”
Section: Resultsmentioning
confidence: 99%
“…Fux et al [ 10 ] pointed out that specific anammox activity (SAA) of anammox was completely inhibited by pH 9.3. Li et al [ 11 ] observed the disintegration of anammox granule at pH 9.0. When the concentration of FA reaches approximately 32.5 mg·L −1 at pH 8.5, anammox bacteria and ammonia oxidising bacteria (AOB) activities are severely inhibited, and the performance of the CANON system deteriorates quickly [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…If the amount of alkali production is uncertain, slightly alkaline inlet water is more suitable. 110,111 It is suitable for slightly alkaline inlet water.…”
Section: Parameter Controlmentioning
confidence: 99%